El trabajo en equipo en el Ministerio de Inclusión Económica y Social [MIES] -Latacunga en el periodo 2023. - Pacheco Córdova, Alexandra Katherine (2023)
The present investigation arose from the lack of teamwork, in the MIES, its objective was to establish the appropriate strategies for the development of capacities and abilities, providing techniques that lead to institutional growth, through the practice of work in team at the Ministry of Economic and Social Inclusion [MIES] located in the canton of Latacunga, period 2023. The study was framed in a quantitative investigation. The design was descriptive in nature. The type of research was field with documentary support. The key informants were selected according to the criteria established by the researchers to the officials of the Institution who were the people who have information on the social reality studied. To collect the information, a survey was used. The information was analyzed and processed through the Google Form program, then the results obtained were presented, analyzed and interpreted. Therefore, relevant information was obtained in the investigation that is not so critical, but is worrisome in the following areas: the opinion of the work team is not taken into account for decision-making, and often they do not have the opportunity to lead a work team, besides, it is difficult for the people who work in this institution to be part of the incentive process. Therefore, strategies are proposed to improve teamwork at MIES Latacunga, oriented in five dimensions such as participation and teamwork, decision making, leadership, skill development and effective communication.